Nitrogen in Stored Poultry Litter: Uric Acid and Xanthine. Issue 6 (1st November 2014) - Mowrer, Jake; Cabrera, Miguel; Rasmussen, Todd; Cassity‐Duffey, Kate
Abstract : Laboratory incubations of four broiler litter (BL) samples at 30°C were performed to investigate the effect of water content on the decay of uric acid nitrogen (UAN) and xanthine nitrogen (XN). UAN and XN concentrations increased in all samples during a period of 1 to 8 d before declining for the remaining 30 d. The increases may be the result of guanine and adenine catabolism. The slopes of linear equations fit to the natural log of the observations from 16 sampling points over 38 d were compared using the GLM procedure in SAS and results indicate that both UAN and XN decay significantly ( p = 0.05) more rapidly with increasing water content (θ). A second study showed significant effects in one of three samples on the decay rate of UAN with additions of flue‐gas desulfurization (FGD) gypsum or alum at a water content of 750 g kg −1 BL. The decay rate of XN was not significantly affected. Finally, a simple two‐point sampling study on the effect of water potential for the estimation of first order rate equation constants showed a positive relationship between the rate of UAN and XN decay over 28 d as a function of water potential (ψ): UAN28days = 0.0054 × ψ + 0.1010 ( r 2 = 0.9987) and XN28days = 0.0066 × ψ + 0.1101 ( r 2 = 0.9285). This is the first study of UAN and XN decay in BL and the findings add to our understanding of mineralizable N from BL.